Effects of Conceptual and Procedural Pedagogical Approaches of Teachers on the Mathematical Performance of Grade 7 Students - Cequeña, Ma. Theresa (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effects of teachers’ conceptual and procedural pedagogical approaches on the mathematical performance of Grade 7 students in selected private secondary schools in the Municipality of Morong, Province of Rizal, during the School Year 2025–2026. Specifically, it examined the extent to which these pedagogical approaches influenced students’ conceptual understanding, mathematical reasoning, problem-solving ability, and classroom engagement, as well as their relationship with mathematical performance. The study employed a descriptive survey research design complemented by documentary analysis. A researcher-made questionnaire-checklist was administered to 125 Grade 7 students selected through convenience sampling from five private secondary schools, namely Jesus My Shepherd Montessori School, Renaissance School of Science and Technology, St. Jerome’s Academy, St. John Hill Academy, and Tomas Claudio Colleges. Documentary analysis of students’ third-quarter Mathematics grades was conducted to determine their level of mathematical performance. Findings revealed that most respondents were female, aged 12–13 years old, with parents who were college graduates, employed in government service, and belonging to families with a monthly income of ₱40,000 and above. Teachers’ conceptual and procedural pedagogical approaches were perceived to have a high effect on students’ mathematical reasoning, problem-solving ability, and classroom engagement. No significant differences were found in students’ perceptions of these pedagogical approaches across most profile variables; however, age and fathers’ educational attainment significantly influenced problem-solving ability. The majority of students achieved outstanding mathematical performance during the third quarter. Furthermore, significant positive relationships were found between teachers’ pedagogical approaches and students’ mathematical performance in terms of conceptual understanding, mathematical reasoning, and classroom engagement, while no significant relationship was established with problem-solving ability. The study concluded that conceptual and procedural pedagogical approaches contribute significantly to students’ mathematical performance and that age and fathers’ educational attainment influence problem-solving ability. It is recommended that schools strengthen mathematics enrichment programs, enhance instructional support, provide continuous teacher professional development, encourage greater parental involvement, and implement the proposed action plan to further improve students’ mathematical performance.
Keywords: Conceptual Pedagogy, Procedural Pedagogy, Mathematical Performance, Conceptual Understanding, Mathematical Reasoning, Problem-Solving Ability, Classroom Engagement, Grade 7 Students